Codon optimization, expression, and purification of the reverse transcriptase enzyme variant MMLV RT2 in Escherichia coli - Sang, Nguyen Van; My, Le Tra; Uyen, Nguyen Thi; Anh , Dang Thi Lan (Vietnam Journal of Biotechnology, 2024)
Moloney leukemia virus reverse transcriptase (MMLV RT) is an important enzyme widely utilized in molecular biology research and various diagnostic testing kits. A previous study demonstrated that variants of MMLV RT containing specific mutations contribute to enhanced stability and increased capability for RNA detection. However, the optimization and increased expression level of MMLV RT variants for large-scale production have not been extensively studied. In this research, the gene segment encoding the MMLV RT variant (E286R/E302K/L435R/D524A) was codon optimized and subcloned into pET-M expression vector. The obtained pET-M MMLV RT2 was transformed into E. coli BL21(DE3) host cell system for over-expression of the MMLV RT2 enzyme. The recombinant enzyme was then purified using nickel affinity chromatography and quantified using the Bradford method. The results revealed significant increase in recombinant enzyme yield, achieving 0.25 g/L in the culture medium. This represents a 1.4-fold increase compared to the 0.175 g/L yield reported in the previous study. Enzyme MMLV RT2 was also evaluated for its activity and was found to have comparable activity to the commercial enzyme Promega and another variant, enzyme MMLV RT1, which carries the D524A mutation and has previously been evaluated for activity. This result suggests that a high expression level of a stable MMLV-RT enzyme variant can be achieved which is beneficial for further improving the production of this important enzyme. The high yield and sustained activity of the MMLV RT2 variant indicate its potential as a reliable and cost-effective alternative for various applications in research and diagnostics. The successful optimization and expression in E. coli highlight the feasibility of large-scale production, potentially lowering costs and improving accessibility for molecular biology applications.